Impact of demographic segmentation and psychographic segmentation on purchase decisions of K beauty products - Eka Dewi Setia Tarigan; Tohap Parulian; Hesti Sabrina; Patar Marbun; Amrin Mulia Utama Nasution (Institute of Computer Science (IOCS), 2023)
The booming development of k pop and k drama has brought many changes to the products purchased by the public. One of the products that are most influenced by k-pop and k-drama are beauty products that are much liked by Indonesian women. Indonesian women really like the beauty of k-pop and k-drama Korean artists so that Korean Hallyu is the current trend. This study used a purposive sampling method with a total sample of 100 people with the sample criteria being women aged 17 years and over who had purchased k beauty products at least three times. This research was conducted to find out whether the demographic segmentation variables consisting of age, occupation, income influence the decision to purchase k beauty products and the psychographic segmentation variables consisting of indicators; values, lifestyle and personality affect consumer purchasing decisions for k beauty products. Partially, each of the demographic and psychographic segmentation variables has a positive and significant effect on the purchasing decision of k beauty products. Simultaneously the two independent variables also have a positive and significant influence so that all hypotheses are accepted.